Long-term exposure to high-altitude chronic hypoxia during gestation induces neonatal pulmonary hypertension at sea level - Emilio A. Herrera; Raquel Riquelme; Germán Ebensperger; Roberto V. Reyes; César E. Ulloa; Gertrudis Cabello; Bernardo J. Krause; Julian T. Parer; Dino A. Giussani; Aníbal J. Llanos (2010)
We determined whether postnatal pulmonary hypertension induced by 70% of pregnancy at high altitude (HA) persists once the offspring return to sea level and investigated pulmonary vascular mechanisms operating under these circumstances. Pregnant ewes were divided into two groups: conception, pregnancy, and delivery at low altitude (580 m, LLL) and conception at low altitude, pregnancy at HA (3,600 m) from 30% of gestation until delivery, and return to lowland (LHL). Pulmonary arterial pressure (PAP) was measured in vivo. Vascular reactivity and morphometry were assessed in small pulmonary arteries (SPA). Protein expression of vascular mediators was determined. LHL lambs had higher basal PAP and a greater increment in PAP after N(G)-nitro-L-arginine methyl ester (20.9 ± 1.1 vs. 13.7 ± 0.5 mmHg; 39.9 ± 5.0 vs. 18.3 ± 1.3 mmHg, respectively). SPA from LHL had a greater maximal contraction to K(+) (1.34 ± 0.05 vs. 1.16 ± 0.05 N/m), higher sensitivity to endothelin-1 and nitroprusside, and persistence of dilatation following blockade of soluble guanylate cyclase. The heart ratio of the right ventricle-to-left ventricle plus septum was higher in the LHL relative to LLL. The muscle area of SPA (29.3 ± 2.9 vs. 21.1 ± 1.7%) and the protein expression of endothelial nitric oxide synthase (1.7 ± 0.1 vs. 1.1 ± 0.2), phosphodiesterase (1.4 ± 0.1 vs. 0.7 ± 0.1), and Ca(2+)-activated K(+) channel (0.76 ± 0.16 vs. 0.30 ± 0.01) were greater in LHL compared with LLL lambs. In contrast, LHL had decreased heme oxygenase-1 expression (0.82 ± 0.26 vs. 2.22 ± 0.44) and carbon monoxide production (all P < 0.05). Postnatal pulmonary hypertension induced by 70% of pregnancy at HA promotes cardiopulmonary remodeling that persists at sea level.